(untitled) (Tanzania Journal for Population studies and Development, 2019)
Smallholder farmers in rural areas need access to institutional support for their effective responses to climate change and related challenges. Rural Local Institutions (RLIs) are very close to farmers and thus have the potential to deliver institutional support and enhance smallholder farmers’ adaptability to climate change and variability. This article responds to two important questions; one, what institutional support that smallholder farmers perceive as relevant in addressing their adaptation challenges? and, how farmers access to that institutional support? To answer these questions, I conducted a study framed within mixed methods design targeting smallholder farmers in 5 villages of Rufiji district in Southern Tanzania. Data collection protocol started with qualitative approaches; Key Informant Interviews (KIIs) and FGDs, to explore the nexus between local understanding of climate change adaptation and institutional roles in adaptation. This informed and was complemented by quantitative survey of 416 farming households obtained through stratified random sampling. Quantitative data analysis was done with the assistance of the Statistical Package for Social Sciencies (SPSS v.16) software. Qualitative analysis followed content analysis framework using Nvivo 12 software. The study found that smallholder farmers perceive a mismatch between their perceived adaptation needs and available institutional support. Farmers identified access to markets, access to climate information; access to agricultural inputs, skills and technologies, land tenure security and access to credits as critical institutional factors necessary for their effective adaptation to climate change and variability challenges. Also that their access to the available institutions for adaptation support is poor due social, environmental, political and economic barriers.The paper argues that RLIs require capacity building to enable them comprehend, design, prioritize, and coordinate farmers’ adaptation actions in relation to other development actions.